Unsur-unsur, Macam-Macam, dan Jenis-Jenis seni Tari untuk Anak Usia Dini - Hilda Zahra Lubis; Nurhayati Nurhayati; Nayla Rizka Irwani; Nurul Fadhilah Ibrahim Nasution (Inovasi Pendidikan dan Anak Usia Dini, 2025)
Early childhood dance education aims to teach kids how to manipulate objects, control and interpret body movements, and cultivate body-mind harmony. This helps kids become more intelligent because it gives them the chance to develop their sensitivity, fantasy, imagination, and creativity. Children's dance education aims to teach them to dance in accordance with their skill level and spiritual nature so that their bodies can become a vehicle for expressing their fantasies and imaginations. Children's dance moves differ from those of adults; they must depict the joyful, pleasurable world of children, with basic movement patterns, topics that are relevant to their lives, and upbeat music.